2021
DOI: 10.1177/10497315211018509
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Programs for Disruptive Child Behavior in China: A Meta-Analysis and Systematic Review

Abstract: Purpose: To synthesize evidence of parenting program effects on disruptive child behavior in China and compare three program approaches: behavioral, relational, and cognitive. Methods: We searched five databases (four English and one Chinese) and identified 45 studies; 29 studies were included in a multilevel meta-analysis (92 effect sizes; total N total = 3,892; M child age = 6.12 years). Results: We found large overall effects on reduced disruptive child behavior ( d = −1.28, 95% CI [−1.86, −0.70], p < .0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 85 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…Other risks of bias explain any crucial concerns about bias not incorporated in the other domains in this tool. In accordance with prior meta-analyses (Hua & Leijten, 2022;Van Aar et al, 2017), if in baseline comparability, a study showed no significant differences between baseline conditions, we considered it as a low risk of bias. If a study showed a substantial difference between groups, we rated it as a high risk of bias.…”
Section: S7 Risk Of Bias In the Included Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Other risks of bias explain any crucial concerns about bias not incorporated in the other domains in this tool. In accordance with prior meta-analyses (Hua & Leijten, 2022;Van Aar et al, 2017), if in baseline comparability, a study showed no significant differences between baseline conditions, we considered it as a low risk of bias. If a study showed a substantial difference between groups, we rated it as a high risk of bias.…”
Section: S7 Risk Of Bias In the Included Studiesmentioning
confidence: 97%
“…In light of some suggestions provided in previous meta-analyses (Hua & Leijten, 2022;Leijten et al, 2019;Leijten et al, 2016;Leijten et al, 2021;Leijten et al, 2018;Piquero et al, 2009;Van Aar et al, 2017), the modified version of the Cochrane Risk of Bias (RoB) tool to assess the methodological quality of included studies was used (Higgins et al, 2011). The following domains regarding the risk of potential bias were considered for each included study.…”
Section: S7 Risk Of Bias In the Included Studiesmentioning
confidence: 99%